La motivación en la Educación Inicial. - Tivan Soria, Melida Lucrecia (2018)
The present research is based on the study about the different techniques of motivation through ludic activities to improve the initial education at Unidad Educative Alonso de Illescas in Guamani parish, in the Quito city, during the academic period 2017-2018. The main research problem was to know how the low rate of motivation affected to the children development in initial education through techniques that help them and make girls and boys strong. This project research provides meaningful learning, children development, ludic strategies and motivation, the research is descriptive. The research was carried out with the teachers and principals through interviews and parents with surveys at Unidad Educative Alonso de Illescas which was expressed on charts and graphics where the information was obtained and verified after analyzing and interpreting. Finally there are some research conclusions and recommendations to create some suggestions to improve the research and learning to know the importance and using the motivational techniques through strategies which help the initial education.